2019
DOI: 10.1177/0972150919870341
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships Between Organizational Culture, Management Control System and Organizational Innovation

Abstract: Organizations consist of numerous tangible and intangible factors. Many of these factors were individually studied in relation to each other, but several factors still need a more thorough investigation. This study aims to examine the direct and indirect effects of organizational culture (OC) on organizational innovation (OI) through the management control system (MCS) as a mediating factor. To achieve this aim, studies were comprehensively conducted in regard to the effects of OC on OI, the effects of OC on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The effect of the organizational culture on the organizational innovation has been empirically tested by the scholars (Martins and Martins, 2002;Abdi and Senin, 2014;Adelekan, 2016;Barbosa, 2014;B€ uschgens et al, 2013;Shahzad et al, 2017;Smit, 2015;Yes ¸il and Kaya, 2012). The existing literature suggests that there are various internal factors that contribute to the OI (Acar and Acar, 2012;Valencia et al, 2010;Alharbi et al, 2019). The OC has played a significant role in shaping organizational innovation (Liu et al, 2010).…”
Section: Relationship Between Drivers Of Innovation and Organizationa...mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the organizational culture on the organizational innovation has been empirically tested by the scholars (Martins and Martins, 2002;Abdi and Senin, 2014;Adelekan, 2016;Barbosa, 2014;B€ uschgens et al, 2013;Shahzad et al, 2017;Smit, 2015;Yes ¸il and Kaya, 2012). The existing literature suggests that there are various internal factors that contribute to the OI (Acar and Acar, 2012;Valencia et al, 2010;Alharbi et al, 2019). The OC has played a significant role in shaping organizational innovation (Liu et al, 2010).…”
Section: Relationship Between Drivers Of Innovation and Organizationa...mentioning
confidence: 99%
“…The results of their demonstrated that combination of innovative organizational culture with flexibility-oriented operations strategy has the strongest influence on a firm's innovation (product innovation and process innovation) and highlighted that flexibility-oriented operations strategy alone is the most significant variable that affects innovation, followed by innovative organizational culture and quality-oriented operations strategy. Alharbi et al (2019) further examined the effects of OC on OI through "management control system" (MCS) as a mediating factor. The results of this study showed that OC had a direct positive and significant effect on OI.…”
Section: Relationship Between Drivers Of Innovation and Organizationa...mentioning
confidence: 99%
“…The article by Lunt reflects the specific features of the implementation of financial controlling systems and different stages of the production process in industrial enterprises [5]. Alharbi, Jamil, Mahmood, Shaharoun considered the system of management controlling as a mediating factor between the influence of organizational culture on organizational innovation in organizations in Saudi Arabia [1]. In the scientific work by Korhonen, Laine, Martinsuo, a study of the perception degree of controlling over the management of uncertainties that accompany the process of making strategic decisions in doing business is carried out, and the need for close cooperation of managers in the formation of a program to control the use of financial resources in conditions of inaccurate information is determined [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to organizational agility, the adhocracy culture and clan stand out, since these cultures are more flexible and adaptive, the latter to a lesser extent. As for the hierarchical culture, which is expected to have a negative effect in changes it can have a positive effect, because the stability, control and order promoted by it can be beneficial in scenarios of crises and uncertainties (Felipe, Roldán, & Leal-Rodríguez, 2017), including the presence of control systems can positively influence the management of innovations (Alharbi, Jamil, Mahmood, & Shaharoun, 2019).…”
Section: Organizational Culturementioning
confidence: 99%